Network pharmacology-based mechanism prediction and pharmacological validation of Bushenhuoxue formula attenuating postmenopausal osteoporosis in ovariectomized mice - Chenjie, Xia (Springer, 2023)
Postmenopausal osteoporosis (PMOP) is a common bone disorder characterized by low bone mineral density and microstructure deterioration [1]. It is estimated that more than 15% of postmenopausal women over 50 years old are suffering in PMOP worldwide [2]. Most of them have low back pain, hunchback and fragility fractures in different degrees [3]. Although there exist a large amount of anti-osteoporosis drugs such as active vitamin D, estrogen receptor modulators, bisphosphonates and parathyroid hormone [4], various undesirable effects limit their application and efficacy [5]. Natural products and herbs attract increasing attention for their potential anti-osteoporosis effects and relative safety